Facilitation of experimental allergic encephalomyelitis by irradiation and virus infection: role of inflammatory cells - Erälinna, J.P. (J Neuroimmunol, 1994)
Infection with an avirulent strain of Semliki Forest virus (SFV-A7) facilitates the development of experimental allergic encephalomyelitis (EAE) in a genetically resistant BALB/c mouse strain. Irradiation which is necessary for EAE induction caused a decrease in the total number of lymphocytes and an increase in CD4(+)/CD8(+) T cell ratio in the spleen of BALB/c mice. EAE induction increased the ratio further until clinical and histological signs of EAE appeared. Entry of perivascular CD4(+) and CD8(+) cells preceded the onset of clinical signs and the appearance of MAC-1(+) cells in the central nervous system (CNS). In the acute phase of EAE, cellular infiltrates, which were sparse, consisted mainly of MAC-1(+) cells and a few CD4(+) and CD8(+) cells. Inflammatory cells gradually disappeared during the recovery phase. SFV-A7 infection after irradiation and EAE induction did not significantly change the CD4(+)/CD8(+) ratio in the spleen or in the CNS infiltrates but enhanced the entry of inflammatory cells into the CNS. Similar perivascular cell influx was also seen in untreated mice infected with SFV-A7. We conclude that observed rapid reduction of splenic mononuclear cells and increase of the CD4(+)/CD8(+) T cell ratio caused by irradiation prior EAE induction are early crucial events in disease induction in this resistant strain of mice. SFV-A7 infection, which further facilitates the development of EAE, does not induce immunoregulatory changes but provides its effect by enhancing the entry of inflammatory cells into the CNS. The combination of these two mechanisms thus effectively breaks the natural resistance against EAE in this genetically resistant mouse strain.